2010
DOI: 10.1364/oe.18.026084
|View full text |Cite
|
Sign up to set email alerts
|

Mathieu beams as versatile light moulds for 3D micro particle assemblies

Abstract: We present tailoring of three dimensional light fields which act as light moulds for elaborate particle micro structures of variable shapes. Stereo microscopy is used for visualization of the 3D particle assemblies. The powerful method is demonstrated for the class of propagation invariant beams, where we introduce the use of Mathieu beams as light moulds with non-rotationally-symmetric structure. They offer multifarious field distributions and facilitate the creation of versatile particle structures. This gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…In the amplitude modulation, as part of the energy is blocked by the holographic elements, the efficiency is about 45% [4]. The phase modulation hologram [15] and the amplitude combined with phase hologram [16] have more design degrees of freedom and higher efficiency. The present diffractive elements can be seen as phase modulation elements to generate Mathieu beams.…”
Section: Gaussian Beam Converted To Mathieu Beammentioning
confidence: 99%
See 1 more Smart Citation
“…In the amplitude modulation, as part of the energy is blocked by the holographic elements, the efficiency is about 45% [4]. The phase modulation hologram [15] and the amplitude combined with phase hologram [16] have more design degrees of freedom and higher efficiency. The present diffractive elements can be seen as phase modulation elements to generate Mathieu beams.…”
Section: Gaussian Beam Converted To Mathieu Beammentioning
confidence: 99%
“…In 2000, Gutierrez-Vega et al demonstrated the existence of optical Mathieu beams [10,11], and they experimentally generated the Mathieu beams by an annular slit [12]. After that, more and more researches on optical Mathieu beams were reported [13][14][15][16]. However, the discussion of Mathieu beams in millimeter wave band has not been seen.…”
Section: Introductionmentioning
confidence: 99%
“…They used the beam with the same intensity in each side so that in the sample area the radiation pressure can be cancelled to obtain better manipulation of particles in 3-D. After the emergence of some technology including spatial light modulator, the researches can easily change the wavefront and thereby receiving more and more new methods of optical trapping .For example. In 2001, Allen used LG which has the orbital angular momentum to rotate the larger calcite and small particles [6], In 2010, Alpmann's group used the Mathiu beam to assemble some elaborate particle micro structures in 3D [7]. In 2011, Mike Woerdemann and his partners utilized Ince-Gaussian beams to manipulate some silica spheres [8].…”
Section: Introductionmentioning
confidence: 99%
“…By performing two dimensional tracking of the position of a particle in each image, its three dimensional coordinates can be reconstructed using parallax. Highspeed video stereo-microscopy has been used in a variety of situations, including the axial position clamping of optically trapped objects [10,11], the observation of optically stacked particles [12], tracking of live algae and artificial non-spherical structures [13,14], and in an optically controlled scanning probe microscope [15].…”
Section: Introductionmentioning
confidence: 99%